Ruang Kosong Ruang Kreasi: Seni Ruang Publik Sebagai Referensi Visual Budaya Tradisi - Figur Rahman Fuad; Endang Sri Handayani; Endri Sintiana Murni (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2021)
The village is the main buffer of the city's culture. The stretching of the village community in developing the potential of human resources and the environment is something that is vital in the development of the city itself. The awareness of citizens to move independently to improve the quality of life is achieved through the arts. This paper wants to describe the collective awareness of residents in Purwodiningratan village in managing the empty space in the alleys of their village. Through the mural art, it is hoped that it can serve as a reminder of how to think and behave, as well as being a connector for traditional values and culture, so that the younger generation always has a foothold in projecting themselves into the future.